Development of Online Academic Portal System Android Based on National University: Development of Online Academic Portal System Android Based on National University - Binsar Pamungkas Batu Bara; M. Iwan Wahyuddin; Agus Iskandar (Institute of Computer Science (IOCS), 2020)
Online academic portal is a system of information section in every tertiary institution. Various academic information ranging from displaying all student information which includes academic activities of students, lecturers and administrative staff. However, the online academic portal system at national universities is still not effective in using web-based services. Therefore, the aim of the researchers is to design an Android-based national university academic portal system so that it can help users / students access online academic portals anywhere without having to open the National University web. Application trial results can display all academic information data with 100% accuracy. In developing the national university's academic portal system, researchers used the waterfall method which is a mature method for researching the development of a system, so that many researchers use this method for research. Then this application is designed using the PHP programming language, PostgreSQL and android studio, this research methodology uses the waterfall method which has several stages of research namely data collection, literature study, application creation, system testing. The results of this study are Android-based online academic portal systems. This research methodology uses the waterfall method which has several stages of research namely data collection, literature study, application making, system testing. The results of this study are Android-based online academic portal systems. This research methodology uses the waterfall method which has several stages of research namely data collection, literature study, application making, system testing. The results of this study are Android-based online academic portal systems.